2018
DOI: 10.1002/cncr.31859
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein and its association with depression in patients receiving treatment for metastatic lung cancer

Abstract: BACKGROUND: Depression is highly prevalent in lung cancer. Although there is a known association between inflammation and depression, this relationship has not been examined in patients with lung cancer who undergo treatment with immune and other targeted drug therapies. Peripheral blood C-reactive protein (CRP), a marker of systemic inflammation, may help identify metastatic lung cancer patients with inflammation-associated depression. METHOD: Patients with metastatic lung cancer undergoing treatment were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 57 publications
2
10
1
1
Order By: Relevance
“…Numerous clinical studies have shown that a significantly higher circulating CRP level was involved in patients with depression (Iob et al., 2020; Osimo et al., 2019; Wang et al., 2018) and has a lower antidepressants efficacy (Li et al., 2019; Zhang, Yue, et al., 2019). Some other works have showed that heart diseases, cancer patients with depressive symptoms also had a higher CRP level (McFarland et al., 2019; Ravona‐Springer et al., 2020). However, there were also conflicting findings showed that CRP was not associated with depressive symptoms nor response to antidepressant treatment (Miller et al., 2019; Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Numerous clinical studies have shown that a significantly higher circulating CRP level was involved in patients with depression (Iob et al., 2020; Osimo et al., 2019; Wang et al., 2018) and has a lower antidepressants efficacy (Li et al., 2019; Zhang, Yue, et al., 2019). Some other works have showed that heart diseases, cancer patients with depressive symptoms also had a higher CRP level (McFarland et al., 2019; Ravona‐Springer et al., 2020). However, there were also conflicting findings showed that CRP was not associated with depressive symptoms nor response to antidepressant treatment (Miller et al., 2019; Zhang et al., 2018).…”
Section: Introductionmentioning
confidence: 95%
“…As reported previously, depression was significantly associated with CRP level and treatment type. 52,53 Depression scores were significantly higher in patients receiving chemotherapy and immunotherapy compared with those receiving targeted therapy (see Table 2). In addition, depression was significantly correlated with NLR (r 5 0.21; P5.017) and absolute neutrophil count (r 5 0.24; P5.008).…”
Section: Resultsmentioning
confidence: 99%
“…According to recent studies, the correlation between inflammatory factors and depressive symptoms is inconsistent across different cancers. For example, in the context of lung cancer, elevated CRP levels are associated with depression in patients with metastatic lung cancer (Mcfarland, Shaffer, Breitbart, Rosenfeld, & Miller, 2018). Conversely, in the context of breast cancer, CRP was not found associated with depressive symptoms (Bower et al., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed a reliable association between inflammatory markers (including CRP, IL-1, and IL-6) and self-reported depressive symptoms, although studies on cancer patients remained extremely limited (Howren, Lamkin, & Suls, 2009). According to recent studies, the correlation between TA B L E 3 Univariate analyses of demographic, inflammatory markers, and physiologic related to behavioral symptoms as measured using the HAMD, HAM-A, and MMSE (Mcfarland, Shaffer, Breitbart, Rosenfeld, & Miller, 2018). Conversely, in the context of breast cancer, CRP was not found associated with depressive symptoms (Bower et al, 2011).…”
Section: Ta B L E 1 Demographic and Clinical Characteristics Of Studymentioning
confidence: 99%